Application of Cooperative Accountability on Cooperatives “Nakula” Ampah (Financial Year 2021-2024) - Palupi, Murraya Putri; Ramadhany, Ridha; Sahay, Marvy Ferdian Agusta; Kumalasari, Intan (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
Accountability is an essential control mechanism in ensuring the achievement of optimal results in the process of providing public services. This process includes understanding tasks and functions, planning, implementation, and evaluation of achievements, all of which can influence the activities of other parties, especially service recipients. This research aims to evaluate the implementation of accountability principles at the "Nakula" Ampah Cooperative during the 2021–2024 Financial Year period, by referring to the Permenkop dan UKM No. 20 /Per/M.KUMK/IX/2015. The research focus is directed at three main dimensions of accountability in cooperatives, namely organizational accountability, service management accountability, and financial accountability. The method used is a descriptive qualitative approach with data collection techniques in the form of direct observation and analysis of cooperative annual report documentation. The research results illustrate that although cooperatives have tried to implement accountability principles according to regulations, there are still a number of weaknesses, especially in low member participation and the delivery of information from management to members. One indicator of weak accountability is the decrease in the value of Remaining Business Results of 37.66% in the last financial year compared to the previous year. This decline shows that there are problems in the efficiency of cooperative business management and the lack of periodic performance evaluations, coupled with the lack of awareness among members to commit to repaying loans on time. This research recommends increasing the management capacity of administrators, digitizing financial reports, and strengthening internal and external monitoring mechanisms to increase accountability and sustainable performance of cooperatives.